kaloja perataan, vasemmalla Piera (Pietari) Proksi - Lagercrantz, Eliel
fyysinen kuvaus: vaaka
Keywords: korit; saamelaiset; perkaaminen; kalastus; Proksi, Piera; Suomi, Enontekiö, Pöyrisjärvi, Enontekiö, Pöyrisjärvi